Highly stable Zn metal anodes enabled by atomic layer deposited Al2O3 coating for aqueous zinc-ion batteries. Issue 16 (7th April 2020) - He, Huibing; Tong, Huan; Song, Xueyang; Song, Xiping; Liu, Jian
Abstract : Nanoscale Al2 O3 coating by an atomic layer deposition technique enabled safe and dendrite-free Zn anodes for rechargeable aqueous zinc-ion batteries. Abstract : Rechargeable aqueous zinc-ion batteries (ZIBs) have attracted increasing attention as an energy storage technology for large-scale applications, due to their high capacity (820 mA h g −1 and 5854 A h L −1 ), inherently high safety, and their low cost. However, the overall performance of ZIBs has been seriously hindered by the poor rechargeability of Zn anodes, because of the dendrite growth, passivation, and hydrogen evolution problems associated with Zn anodes. Herein, Al2 O3 coating by an atomic layer deposition (ALD) technique was developed to address the aforementioned problems and improve the rechargeability of Zn anodes for ZIBs. By coating the Zn plate with an ultrathin Al2 O3 layer, the wettability of Zn was improved and corrosion was inhibited. As a result, the formation of Zn dendrites was effectively suppressed, with a significantly improved lifetime in the Zn–Zn symmetric cells. With the optimized coating thickness of 100 cycles, 100Al2 O3 @Zn symmetric cells showed a reduced overpotential (36.5 mV) and a prolonged life span (over 500 h) at 1 mA cm −2 . In addition, the 100Al2 O3 @Zn has been verified in Zn–MnO2 batteries using layered δ-MnO2 as the cathode and consequently exhibits superior electrochemical performance with a high capacity retention of 89.4% after over 1000 cycles at a current density of 1 mA cm −2 (3.33C for MnO2 ) was demonstrated. It is expected that the novel design of Al2 O3 modified Zn anodes may pave the way towards high-performance aqueous ZIBs and shed light on the development of other metal anode-based battery systems.